Determination of survey boat “heave” motion with the use of RTS technique - Popielarczyk, Dariusz (International Conference “Environmental Engineering”, 2017)
The paper presents analysis of determination of vertical movement of the surveying boat called “heave” with the use of Robotized Total Station (RTS) technique. The classical geodetic Total Station was used for sub-centimeter calculation of water level changes during hydroacoustic measurements on the fragment of Vistula river behind the dam and hydropower in Włocławek in Poland. The power station work causes up to 1.7 m movement of vertical reference water surface in aspect of local bathymetric survey. The experimental, hydrographic surveys on the river were conducted where the water level was changing significantly over time depending on the operational sched ule of the power plant. Verified hydrographic data had to be brought to the common water level. To determine the final water level, data on the height of the Robotized Total Station prism positioned on the boat during sounding was considered. The RTS technique with 0.02–0.05 m vertical accuracy proved to be very useful and essential in engineering inland bathymetric measurements.
Keywords: bathymetry; “heave”; Robotized Total Station